1997
DOI: 10.1029/96jd03457
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous uptake of ClONO2 and N2O5 by sulfuric acid solutions

Abstract: Abstract. A droplet train apparatus has been used to measure the heterogeneous reactive uptake of gaseous N20 s and C1ONO2 by concentrated sulfuric acid solutions. H2SO 4 concentrations in the range of 39 to 69 wt % were investigated between 229 and 260 K. Uptake rates normalized to the gas-liquid collision frequency, 3/0, for N2Os ranged from 0.086 to 0.16, decreasing moderately with increasing temperature and decreasing H2SO 4 concentration. Uptake rates for C1ONO2, measured over a slightly narrower concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
132
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(145 citation statements)
references
References 89 publications
13
132
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] The reported uptake coefficients for the reaction with solid NaCl are less consistent, ranging from less than 10 À4 to greater than 2.5 Â 10 À3 . The yield of ClNO 2 (and hence, the branching ratio between ClNO 2 and HNO 3 /HCl) is quite variable in the studies of the solids and the aerosol particles, ranging from 31 to 100%.…”
Section: à2mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The reported uptake coefficients for the reaction with solid NaCl are less consistent, ranging from less than 10 À4 to greater than 2.5 Â 10 À3 . The yield of ClNO 2 (and hence, the branching ratio between ClNO 2 and HNO 3 /HCl) is quite variable in the studies of the solids and the aerosol particles, ranging from 31 to 100%.…”
Section: à2mentioning
confidence: 99%
“…In the works of Robinson et al [6] and Hanson and Ravishankara [7] the mass-accommodation coefficient, diffusion process into the liquid, and reaction in the bulk are connected in the frame of a ''resistor'' model. Based on the well-developed resistance model, the uptake and accommodation process are connected through Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Models must parameterize the reaction probability based on laboratory studies that use highly idealized particle compositions, and then also make assumptions about the mixing state of atmospheric particles. Laboratory studies have shown that γ (N 2 O 5 ) can span several orders of magnitude depending upon particle composition and phase state (Hallquist et al, 2003;Hu and Abbatt, 1997;Kane et al, 2001;McNeill et al, 2006;Mozurkewich and Calvert, 1988;Robinson et al, 1997). Particulate water, chloride, nitrate, and organic particle coatings can all have effects on the N 2 O 5 reaction probability (Bertram and Thornton, 2009;Bertram et al, 2009b;Folkers et al, 2003;Mentel et al, 1999;Park et al, 2007;Thornton et al, 2003;Thornton and Abbatt, 2005;Wahner et al, 1998).…”
Section: T P Riedel Et Al: Direct N 2 O 5 Reactivity Measurements mentioning
confidence: 99%